An analysis of the respective contributions of husband and wife in farming households in Kenya to decisions regarding the use of income: A multinomial logit approach. (November 2020) - Osanya, Jessica; Adam, Rahma I.; Otieno, David Jakinda; Nyikal, Rose; Jaleta, Moti
Abstract: This paper analyzes the socio-economic characteristics of households that affect husbands and wives' contributions to decisions regarding the use of income from crop and livestock sales in Kenya. Using a sample of 276 households, we apply a multinomial logit model to assess factors affecting decision-making. Results show that husbands make most decisions concerning agriculture, while wives mainly decide on daily household expenditure. Higher education levels were found to increase women's involvement in decision-making on income use. Group membership had a positive effect on joint decision-making on income use. The study recommends improving women's access to education, which will improve their access to productive resources, hence their decision-making power. Providing incentives for members of agricultural groups can provide avenues for learning. Gender-transformative approaches that empower women and sensitize men to allow space for women to engage in decision-making, can have an impact in improving the decision-making capacity of women in households.